Dynamic trading and asset prices : Keynes vs. Hayek - Giovanni Cespa; Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2009)
We investigate the dynamics of prices, information and expectations in a competitive, noisy, dynamic asset pricing equilibrium model. We show that prices are farther away from (closer to) fundamentals compared with average expectations if and only if traders over- (under-) rely on public information with respect to optimal statistical weights. Both phenomena, in turn, occur whenever traders speculate on short-run price movements. For a given, positive level of residual payoff uncertainty, over-reliance on public information obtains if noise trade displays low persistence. This defines a Keynesian region; the complementary region is Hayekian in that prices are systematically closer to fundamentals than average expectations. The standard case of no residual uncertainty and noise trading following a random walk is on the frontier of the two regions and identifies the set of deep parameters for which traders abide by Keynes' dictum of concentrating on an asset long term prospects and those only. The analysis explains accommodation and trend chasing strategies as well as momentum and reversal.
Keywords: G10; G12; G14; 330; efficient market hypothesis; long and short-term trading; average expectations; higher order beliefs; over-reliance on public information; opaqueness; momentum; reversal; Börsenkurs; Kapitalmarkttheorie; Effizienzmarktthese; Noise Trading; Wertpapierhandel; Informationsverhalten; Erwartungstheorie; Theorie